Job Satisfaction in Mediating the Influence of Transformational Leadership and Work Discipline on the Performance of Employees - Ida Bagus Udayana Putra; Putu Ngurah Suyatna Yasa; Astuti Astuti; Ida Bagus Gede Parama Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Employee performance is a pivotal factor in organizational success, as it directly influences the achievement of strategic goals. This study aims to analyze the mediating role of job satisfaction in the relationship between transformational leadership and work discipline on employee performance at the Raja Ampat Regency Education Office. Utilizing a saturated sampling technique, the study involved a population of 47 employees. Data were analyzed using inferential statistics via Structural Equation Modelling-Partial Least Squares (SEM-PLS). The findings indicate that both transformational leadership and work discipline exert a positive, significant direct effect on employee performance. While work discipline significantly influences job satisfaction, transformational leadership was found to have a positive but insignificant impact on it. Furthermore, job satisfaction significantly enhances employee performance. Mediation analysis reveals that job satisfaction does not mediate the relationship between transformational leadership and employee performance. In contrast, job satisfaction partially mediates the influence of work discipline on employee performance. These results suggest that while leadership and discipline are critical, the impact of discipline on performance is further strengthened when employees experience higher job satisfaction. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 16: Peace, Justice, and Strong Institutions